2021
DOI: 10.1186/s13014-021-01955-7
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of osimertinib plus cranial radiotherapy compared to osimertinib alone in NSCLC patients with EGFR-activating mutations and brain metastases: a retrospective study

Abstract: Background The study aimed to compare the efficacy of osimertinib plus cranial radiotherapy (RT) with osimertinib alone in advanced non-small-cell lung cancer (NSCLC) patients harboring epidermal growth factor receptor (EGFR) mutations and brain metastases (BMs). Methods The clinical data of advanced NSCLC patients with BMs who received osimertinib were retrospectively collected. The patients were assigned to one of the two groups according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…The overall AE probability was 21.6% (35/162) in this study, with the highest incidence of Rash (28.6%, 10/35) and Diarrhea (11.4%, 4/35). The overall safety was reliable, which was consistent with previous studies [30] .…”
Section: Discussionsupporting
confidence: 91%
“…The overall AE probability was 21.6% (35/162) in this study, with the highest incidence of Rash (28.6%, 10/35) and Diarrhea (11.4%, 4/35). The overall safety was reliable, which was consistent with previous studies [30] .…”
Section: Discussionsupporting
confidence: 91%
“…However, for patients with L858R mutation and BM, a retrospective Chinese study analyzing 61 patients showed that median OS was significantly better (29.2 versus 18.8 months) if osimertinib was combined with cranial radiotherapy. 31 This can also be suggested from our data as, although the number of patients was low, 40% of patients with L858R and BM died within 4 months, the minority of these patients received local treatment for their BM before start of systemic treatment. It is not clear whether these patients died from neurological progression (i.e.…”
Section: Discussionsupporting
confidence: 60%
“…Recently, efforts have been done to combine last generation systemic therapies to WBRT-SIB in patients with multiple BMs also compared to standard WBRT in NSCLC patents (12,14). The number of treated patients is very small, and a real difference of the addition of the drug to WBRT versus a monotherapy was not detected.…”
Section: Discussionmentioning
confidence: 99%